1976
DOI: 10.1148/121.2.315
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Calcifications in Severe Chronic Renal Disease and their Relationship to Dialysis Treatment, Renal Transplant, and Parathyroidectomy

Abstract: The incidence, distribution, and progression of arterial calcification in severe chronic renal disease were studied from 364 skeletal survey examinations in 152 patients (ages 15-60). The incidence increased from 30% in the 15-30 age group to 50% in the 40-50 group. The earliest and commonest site of calcification was the ankles, followed in frequency by the abdominal aorta, feet, pelvis, and hands and wrists. Progression occurred in 36% of the nondialyzed, 19% of the peritoneally dialyzed, 13% of the post-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
4

Year Published

1978
1978
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 13 publications
3
35
1
4
Order By: Relevance
“…Vascular calcification (VC), especially in the arterial media, is probably a major contributor to arteriosclerosis in CKD (127)(128)(129)(130). Numerous autopsy and radiologic studies in the past several decades have demonstrated high rates of calcification of peripheral and central arteries (131)(132)(133)(134)(135)(136)(137)(138)(139)(140), and coronary artery calcification is even common and progressive in young adult hemodialysis patients (141). VC is probably primarily due to abnormal mineral metabolism that is seen in renal failure (141)(142)(143)(144)(145), perhaps through a complex process involving osseous metaplasia of the vascular wall components (118,119,146).…”
Section: Pathophysiology Of Cvd In Ckdmentioning
confidence: 99%
“…Vascular calcification (VC), especially in the arterial media, is probably a major contributor to arteriosclerosis in CKD (127)(128)(129)(130). Numerous autopsy and radiologic studies in the past several decades have demonstrated high rates of calcification of peripheral and central arteries (131)(132)(133)(134)(135)(136)(137)(138)(139)(140), and coronary artery calcification is even common and progressive in young adult hemodialysis patients (141). VC is probably primarily due to abnormal mineral metabolism that is seen in renal failure (141)(142)(143)(144)(145), perhaps through a complex process involving osseous metaplasia of the vascular wall components (118,119,146).…”
Section: Pathophysiology Of Cvd In Ckdmentioning
confidence: 99%
“…Aortic calcification occurs in very high incidence in patients with chronic renal failure, especially in hemodialysis patients [18, 19]. High serum phosphate, unchanged serum calcium and high Ca × P products in the control group may have caused metastatic calcification, especially aortic calcification.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Kro nik böb rek yet mez lik li has ta lar da vas kü ler kal si fi kasyon di rekt gra fi ler de ilk ola rak 1976 yı lın da ta nım -lan mış tır. 3 1969-1977 yıl la rı ara sın da ölen he mo di ya liz has ta la rı nın otop si le ri in ce len di ğin de vas kü ler kal si fi kas yon sık lı ğı nın %50-80 gi bi dikka te de ğer bir şekil de yük sek oran lar da ol du ğu tespit edil miş tir. 4,5 Kal si fi kas yon ge nel lik le bü yük ve kü çük ar terler de, myo kar di um ve kalp ka pak la rın da iz le nen bir du rum ol mak la bir lik te tüm yu mu şak do ku larda da kal si fi kas yon ge li şe bi lir.…”
Section: Kro Ni̇k Böb Rek Yet Mez Li̇ ğİ Ve Vas Kü Ler Kal Si̇ Fi̇ Kas Yonunclassified